Dampak Sosial Budaya Dari Program Keluarga Harapan Dan Bantuan Pangan Non Tunai Di Kabupaten Gunung Kidul - Sumarni, Sumarni (Jurnal Ilmu Administrasi Negara (JUAN), 2020)
Program Keluarga Harapan and Bantuan Pangan Non Tunai is Conditional Cash Transfer given by the central system. This system is considered capable of reducing poverty. Data says that this program is one of the highest APBN budget allocations, each year experiencing an increase in budget and recipient figures, this certainly It is expected that along with the impacts resulting from the policy itself, both socio-economic and socio-cultural impacts, the purpose of this research is to see how much impact this policy has and what socio-cultural impacts are generated by this policy, the research method uses mixed methods, data collection techniques through interviews and also online surveys, the results of this research is that this policy has a socio-cultural impact with point 3 with the criteria of strength, closeness and also the amount of help, the two researchers found that there are some impacts that arise from this policy namely culture " ng andalke â€ this condition recipients lack the enthusiasm to work if during disbursement, they will spend the funds first, when the funds have been used up then they are more active to work again, and the other condition there are the community who do not get help the emergence of social jealousy due to the large number of beneficiaries who do not meet the criteria even more recipients are compared to those who don't.